2019
DOI: 10.1093/jb/mvz054
|View full text |Cite
|
Sign up to set email alerts
|

Propofol alleviates oxidative stress via upregulating lncRNA-TUG1/Brg1 pathway in hypoxia/reoxygenation hepatic cells

Abstract: Reducing oxidative stress is an effective method to prevent hepatic ischaemia/reperfusion injury (HIRI). This study focuses on the role of propofol on the oxidative stress of hepatic cells and the involved lncRNA-TUG1/Brahma-related gene 1 (Brg1) pathway in HIRI mice. The mouse HIRI model was established and was intraperitoneally injected with propofol postconditioning. Hepatic injury indexes were used to evaluate HIRI. The oxidative stress was indicated by increasing 8-isoprostane concentration. Mouse hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…[27,35] Specifically, PPF alleviates oxidative stress by regulating the TUG1/Brg1 pathway in hepatocytes exposed to H/R. [36] PPF exhibits protective effects in I/R-induced liver injury by increasing miR-133a-5p expression and decreasing MAPK6 expression. [37] In this study, it was found that PPF could decrease the expression of MALAT1 and increase the expression of miR-206.…”
Section: Discussionmentioning
confidence: 98%
“…[27,35] Specifically, PPF alleviates oxidative stress by regulating the TUG1/Brg1 pathway in hepatocytes exposed to H/R. [36] PPF exhibits protective effects in I/R-induced liver injury by increasing miR-133a-5p expression and decreasing MAPK6 expression. [37] In this study, it was found that PPF could decrease the expression of MALAT1 and increase the expression of miR-206.…”
Section: Discussionmentioning
confidence: 98%
“…BRG1-mediated Nrf2/HO-1 transcriptional activation is important for oxidative stress injury induced by ischemia/reperfusion (I/R) or hypoxia/reoxygenation (H/R). Propofol alleviates oxidative stress in anoxia/reoxygenated hepatocytes through the lncRNA-TUG1/BRG1 pathway [ 40 ]. Knockdown of BRG1 inhibited HO-1 expression, thereby weakening the protective effect of propofol postconditioning on hepatic ischemia/reperfusion injury (HIRI) [ 41 ].…”
Section: Brg1 In Oxidative Stress Signalingmentioning
confidence: 99%
“…Excessive oxidative stress and excessive inflammatory response are well recognized as another contributory factor in the pathology of HIRI ( 30 ). Thus, the present study examined the protective effects of Sevo on oxidative stress.…”
Section: Resultsmentioning
confidence: 99%